PENERAPAN INTERNET OF THINGS (IOT) PADA ROBOT PELAYANAN MENGGUNAKAN MQTT (MESSAGE QUEUING TELEMETRY TRANSPORT) UNTUK MONITORING REALTIME - Harry Abi Bayu; Mhd. Zulfansyuri Siambaton; Aulia Ichsan (PT. Hasba Edukasi Mandiri, 2026)
Internet of Things (IoT) technology has driven innovation in automation systems, including service-based robotic applications. This research aims to design and implement an IoT-based service robot system capable of receiving real-time commands and performing automatic navigation to designated locations. The system is developed using multiple ESP32 microcontrollers interconnected via a Wi-Fi network and communicating through the Message Queuing Telemetry Transport (MQTT) protocol. The research methodology includes system architecture design, hardware and software implementation, and system testing. The robot navigation is designed using a Finite State Machine (FSM) approach based on time-based navigation, while obstacle detection is handled using an ultrasonic sensor. A web-based user interface is implemented to send commands and monitor the robot's status in real time. The results show that the MQTT-based communication system is able to transmit and receive data reliably with delay values within acceptable limits for real-time applications. Furthermore, the robot successfully navigates to the target tables and returns to the starting position according to the designed system, while also responding effectively to obstacles detected along its path.In conclusion, this study demonstrates that the integration of IoT, FSM-based control, and time-based navigation can be effectively applied to a service robot system with a high level of operational success.